2017
DOI: 10.22159/ijpps.2017v9i7.18046
|View full text |Cite
|
Sign up to set email alerts
|

POTENTIAL ROLE OF MILK THISTLE SEED AND ITS OIL EXTRACTS AGAINST HEART AND BRAIN INJURIES INDUCED BY Γ-Radiation EXPOSURE

Abstract: Objective: This study aimed to investigate the protective effect of Silybum marianum (S. marianum) seeds extract its oil fraction against damage effect of γ-radiation in female albino rats.Methods: Ultrasonic-assisted extraction was used for the extraction of S. marianum seeds. Lipid patterns of S. marianum seeds oil were elucidated using gas chromatography-mass spectrometry (GC-MS). S. marianum seeds extract was analyzed using high-performance liquid chromatography (HPLC). Malondialdehyde (MDA), reduced gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…This result is in accordance with Sarin and coauthors [34] and Newairy and coauthors [35], who referred dyslipidemia to aluminium accumulation in the liver. Our results showed a decline in LDH and CPK activities post irradiation and this data is in agreement with Sherif and coauthors [36], but it is disagreed with Mansour and Tawfik [37] who reported that γ-radiation produced significant elevations in CPK and LDH. So, the great production of free radicals and lipid peroxides might cause the leakage of the cytosolic enzymes, including the aminotransferases, creatine kinase and phosphatase enzymes.…”
Section: Discussionsupporting
confidence: 81%
“…This result is in accordance with Sarin and coauthors [34] and Newairy and coauthors [35], who referred dyslipidemia to aluminium accumulation in the liver. Our results showed a decline in LDH and CPK activities post irradiation and this data is in agreement with Sherif and coauthors [36], but it is disagreed with Mansour and Tawfik [37] who reported that γ-radiation produced significant elevations in CPK and LDH. So, the great production of free radicals and lipid peroxides might cause the leakage of the cytosolic enzymes, including the aminotransferases, creatine kinase and phosphatase enzymes.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, a marked increase was observed in MDA levels following whole-body X-ray exposure (Table 1). Various studies have reported that exposure to ionizing radiation results in damage to membrane lipids [37][38][39]. In addition, the formation of hydrophilic peroxide from lipophilic unsaturated fatty acid changes membrane dynamics and results in loss of structural as well as functional integrity of membrane [40].…”
Section: Discussionmentioning
confidence: 99%